European company survey 2009 overview - Riedmann, Arnold; Gyes, Guy van.; Roman, Amelia; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2010)
The second large-scale European-wide establishment survey launched by the European Foundation for the Improvement of Living and Working Conditions (Eurofound) - known as the European Company Survey 2009 (ECS 2009) - focuses on two topics in the field of company policies that are widely debated in the EU: flexibility practices and employee participation at the workplace. Following on from the first Eurofound establishment survey in 2004-2005, the ECS 2009 was carried out across the 27 EU Member States and in the candidate countries of Croatia, the Former Yugoslav Republic of Macedonia and Turkey. In more than 27,000 establishments with 10 or more employees of both the private and the public sectors, human resources managers and employee representatives - where available - were interviewed about flexibility measures applied at the establishment and the involvement of employee representatives in their set-up. The survey covers different forms of working time flexibility (flexitime and working time account systems, part-time work, overtime work and work at unusual hours), the application of non-permanent employment contracts (external flexibility), aspects of wage flexibility as well as modes of enhancing the employability of staff for different tasks (functional flexibility).
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Flextime -- European Union countries; Industrial relations -- European Union countries; Labor market -- Europe; Electronic books